Rich dad, poor dad : what the rich teach their kids about money-- that the poor and middle class do not! - Kiyosaki, Robert T.; Lechter, Sharon L. (New York : Warner Business Books, 2000)
(3z(BRich Dad, Poor Dad(3y (Bchronicles the story of two dads, the author$1 (Bs own father, who was the superintendent of education in Hawaii and who ended up dying penniless, and the author's best friend$1 (Bs father (and Kiyosaki$1 (Bs mentor growing up), who dropped out of school at age 13 and went on to become one of the wealthiest men in Hawaii. Kiyosaki uses the story of these two men and their varying financial strategies to illustrate the need for a new financial paradigm in order to achieve financial success in the new millennium.s
86923, 112313
Keywords: Finance, Personal; Investments; Rich people